2013
DOI: 10.1021/nn303824j
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanical Heterogeneity of the Erythrocyte Membrane Reveals Hallmarks of Membrane Stability

Abstract: The erythrocyte membrane, a metabolically regulated active structure that comprises lipid molecules, junctional complexes, and the spectrin network, enables the cell to undergo large passive deformations when passing through the microvascular system. Here we use atomic force microscopy (AFM) imaging and quantitative mechanical mapping at nanometer resolution to correlate structure and mechanics of key components of the erythrocyte membrane, crucial for cell integrity and function. Our data reveal structural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…Moreover, reduced ATP depletion can maintain RBCs morphology in response to Cr 6+ exposure, suggesting that ATP depletion may not be just a by-pass result of increased Ca 2+ influx during the process of Cr 6+ -induced eryptosis. This result was consistent with the report that ATP is important for maintaining membrane dynamic equilibrium and cytoskeleton in RBCs [43,45,49]. The ROS toxicity effect on RBCs after Cr 6+ exposure was not reversed by additional antioxidants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, reduced ATP depletion can maintain RBCs morphology in response to Cr 6+ exposure, suggesting that ATP depletion may not be just a by-pass result of increased Ca 2+ influx during the process of Cr 6+ -induced eryptosis. This result was consistent with the report that ATP is important for maintaining membrane dynamic equilibrium and cytoskeleton in RBCs [43,45,49]. The ROS toxicity effect on RBCs after Cr 6+ exposure was not reversed by additional antioxidants.…”
Section: Discussionsupporting
confidence: 93%
“…Rapid ATP depletion is caused by excessive activation of the Ca 2+ pump and has been considered a result of Ca 2+ influx [38,44]. A recent study reported that ATP depletion affects phosphorylation levels of the 4.1R and spectrin proteins, which are key proteins in the RBCs cytoskeletal network [45]. Depletion of the ATP level to below 25% that of normal RBCs eventually leads to cell membrane skeleton fracture and irreversible eryptosis of spike-shaped RBCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Scheuring et al found that the ability of ATP to modulate RBC membrane stability is to govern the different components as a unit instead of to influence the mechanical properties of individual components themselves. 64 They also found that the mechanical properties of membrane proteins can be considered as the signature of molecular bio-function. 65 In addition to native proteins, the misfolding amyloid proteins have also been characterized by advanced FS.…”
Section: Advanced Fs-based Force-volume Mappingmentioning
confidence: 99%
“…Since the advent, researchers have applied PFT imaging to investigate the physicochemical properties of different biological samples, e.g., membrane proteins (bacteriorhodopsin on the purple membrane of bacterial (Rico et al, 2011;Medalsy et al, 2011), erythrocyte membrane (Picas et al, 2013) and living cells (keratinocyte (Heu et al, 2012), yeast , and Escherichia coli bacteria . However, these researches were commonly performed using ordinary tips (Heu et al, 2012;Rico et al, 2011;Medalsy et al, 2011;Picas et al, 2013) that cannot identify the specific membrane proteins on the cell surface. In recent studies, researchers have applied PFT imaging to investigate the molecular interactions on bacterial cells using functionalized tips.…”
Section: Introductionmentioning
confidence: 99%